Banning tobacco sales and advertisements near educational institutions may reduce students' tobacco use risk: evidence from Mumbai, India. Issue Volume 24:Issue e1(2015) (19th August 2013) - Mistry, Ritesh; Pednekar, Mangesh; Pimple, Sharmila; Gupta, Prakash C; McCarthy, William J; Raute, Lalit J; Patel, Minal; Shastri, Surendra S
Abstract : Background: India's Cigarettes and Other Tobacco Products Act bans tobacco sales and advertisements within 100 yards of educational institutions. In school-adjacent neighbourhoods in Mumbai, we assessed adherence to these policies and whether tobacco vendor and advertisement densities were associated with students' tobacco use. Methods: High school students' tobacco use was measured using a multistage cluster sampling survey (n=1533). Field geographic information systems data were obtained for all tobacco vendors and advertisements within 500 m of schools (n=26). Random-effects multilevel logistic regression was used to estimate associations of tobacco vendor and advertisement densities with ever tobacco use, current smokeless tobacco use and current tobacco use. Results: There were 1741 tobacco vendors and 424 advertisements within 500 m of schools, with 221 vendors (13%) and 42 advertisements (10%) located within 100 m. School-adjacent tobacco vendor density within 100 m was not associated with the tobacco use outcomes, but tobacco advertisement density within 100 m was associated with all outcomes when comparing highest to lowest density tertiles: ever use (OR: 2.01; 95% CI 1.00 to 4.07), current use (2.23; 1.16, 4.28) and current smokeless tobacco use (2.01; 1.02, 3.98). Tobacco vendor density within 200, 300, 400 and 500 m of schools was associated with current tobacco use and current smokeless tobacco use, but not ever use. Conclusions: The tobacco sales ban near educational institutions could be expanded beyond 100 m. Greater enforcement is needed regarding the current bans, particularly because advertisement density within 100 m of schools was associated with all students' tobacco use outcomes.